Penerapan Alat Cuci Tangan Otomatis untuk Masyarakat Kelurahan Bukit Merapin Kota Pangkalpinang - Rika Favoria Gusa; Dede Naruari; Welly Yandi (Abimanyu : Jornal of Community Engagement, 2021)
Since the beginning of 2020, the world has faced an outbreak of the Corona Virus Disease (COVID-19). Corona virus can be transmitted when someone touches nose, mouth or eyes after touching a surface that has been contaminated with the virus from a person who coughs or sneezes. To prevent contracting COVID-19, one way that can be done is to get used to washing hands with soap and running water, especially when in public places. With the automatic hand washing equipment, people do not need to touch the water tap to wash their hands, thus minimizing the possibility of spreading the virus. The hand washing device is made consisting of a water tap that can flow water automatically when an ultrasonic sensor captures hand movements around the mouth of the faucet and a water reservoir that can be filled automatically based on the reading of the water level by the ultrasonic sensor. This automatic hand washing tool has been used in sub-district office and mosque in Bukit Merapin sub-district, Pangkalpinang.